Simplified model for static stress analysis of straight eccentric lug subjected to cosine distribution pressure. (December 2021) - Xu, Wenliu; Wang, Licheng
Abstract: A simplified analytical method is presented for predicting static stress distribution of the straight eccentric lug subjected to cosine distribution pressure. The method of analysis is only suitable for the situation where the predicted peak stress in the straight eccentric lug remains at or below the yield stress of the steel material used for it. In this method, the Castigliano's theorem is used to determine the internal force distribution of the straight eccentric lug, and the bipolar coordinate system is introduced to analyze the stress state of the straight eccentric lug under bending moment. By comparing with the FEM's results, it is proved that the present method can give a good precision in predicting the stress distribution of the straight eccentric lug subjected to the cosine distribution pressure. And the peak circumferential tension stress of the straight eccentric lug is observed at the edge of lug hole above the pin. Moreover, the effects of inner radius/outer radius ratio, distance between the two circle centers, and lug thickness to the peak tension stress are investigated. Based on contrastive analysis, it is concluded that the peak tension stress can be reduced either by increasing the inner radius/outer radius ratio and lug thickness, or by decreasing the distance between the two circle centers.